Kinematic study of left arm during golf swing - Teu, K. K.; Kim, W.; Fuss, F. K.; Tan, J. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
The knowledge of how golfer uses the different segmental motion to strike the ball may provide valuable information. The objective of this study is to ascertain the contribution of the segmental rotations to the club head speed of a golf swing. The method provides an efficient approach of assessing the effectiveness of the arm segment rotations in producing club head speed. This method can be easily applied to other actions to describe and assess the contribution of segmental rotations to performance. In general, the method provides convenient access to movement recording and analyses. This method of analysis provides detailed information which may be omitted with other approaches.